Suicide attempts as a cause of pelvic injuries during the COVID-19 pandemic - Rezek, Jan; Šídlo, Kryštof; Džupa, Valér; Horáček, Jiří; Hulín, Ivan (Bratislavské lekárske listy, 2022)
OBJECTIVES: We decided to compare the incidence and spectrum of pelvic fractures in 2020 affected by the anti-pandemic measures due to COVID-19 with previous years 2018 and 2019. METHODS: This retrospective study included 391 patients treated at the author’s clinic for pelvic fractures. From the medical records we recorded gender, age, mechanism of injury, trauma energy, fracture type based on the AO classification and severity of injury. RESULTS: As expected, we observed no difference in the number of fractures caused by simple falls. However, we failed to prove a reduction in the number of high-energy injuries. In contrary, we observed an increase in the number of high-energy injuries in the period between lockdowns (p=0.0375). A surprising result was a dramatic increase in suicide attempts as a cause of pelvic fractures, with 6 (2.2 %) in 2018 and 2019 compared to 13 (10 %) in 2020 alone (p=0.0017). CONCLUSION: We observed the increased number of suicidal attempts only on a limited number of specific patients with pelvic fractures; therefore, we cannot formulate any general conclusions regarding the incidence of suicide during the COVID-19 pandemic. Nevertheless, we consider this to be a warning signal highlighting the worsened population mental health due to COVID-19 pandemic (Tab. 2, Fig. 1, Ref. 34).
Keywords: Female; lidé středního věku; Suicide, Attempted; pánev; rány a poranění; mužské pohlaví; Retrospective Studies; Wounds and Injuries; retrospektivní studie; Humans; dospělí; Pelvis; lidé; Middle Aged; senioři; ženské pohlaví; pokus o sebevraždu; Aged; Adult; Male; COVID-19